Experiências de movimento e a formação inicial em educação física: implicações nas vivências do currículo - Trentin, Daiane Toigo (Universidade do Vale do Rio do Sinos, 2007)
This research aims to analyze and understand the implications of the movement experiences learned by students of Physical Education throughout their participation in the development of the course curriculum. To meet this goal, we have sought to: learn the movement experiences of the students under this study from their childhood onwards in different environments (streets, parks, nursery schools, school, home, university, clubs, etc); establish the motives that have caused them to join a Physical Education course in its preliminary level, as well as their expectations towards it; understand how students of Physical Education follow and live through the curriculum content. Four students of Physical Education – of a teaching degree – from a University in Caxias do Sul, have participated in this study. Two interviews have been conducted with each of these students, after which they have been analyzed under an exegetical procedure. The results have been discussed based on authors such as Carrero da Costa et a
Keywords: currículo; ensino superior; formação profissional; professor; educação física; movement experiences; teacher training; physical education; Ciências Humanas